Electronic Funds Transfer and National Banks (Washington University Law Quarterly, 1977)
The controversial growth of electronic funds transfer (EFT) has caused a series of economic dislocations and inequities. The dispute is caused not by differences in academic or philosophical opinion, but rather by competing economic forces attempting to protect their legitimate interests. Much of the controversy concerns four important issues: the application of state and federal branching laws, the sharing of EFT terminals, the government’s role in EFT development, and the economics of EFT.
Keywords: Commercial law